Terminator 2 [videorecording (Blu-Ray)] : judgment day - Schwarzenegger, Arnold; Hamilton, Linda, 1956-; Patrick, Robert, 1958-; Morton, Joe, 1947-; Furlong, Edward, 1977-; Cameron, James, 1954- (Studio Canal ; Lionsgate, 2009)
Two cyborgs are sent from the future, but while one is on a mission to kill John Connor, who will lead the resistance movement in the future against the machines, the other is sent to protect Connor.